Media Diplomacy in the Cultural Convergence of the Nowruz Region - Mesbah, A. Basir; Hafid, Ghawsuddin; Altafe, Sayed Borhan (Multidisciplinary Journal of Education , Economic and Culture, 2026)
Nowruz is considered the greatest ancient ritual in the countries of Southwestern Asia and some other parts of the world, and it is referred to as the Civilization of Nowruz. In this civilization, modernity, combating ignorance, moderation, truthfulness, greenery, and separation from ugliness are distinctive elements. This research seeks to answer the question of how it is possible to enable cultural convergence among the countries of the Nowruz sphere by applying a proper media strategy. The findings of the study, conducted with an analytical-descriptive approach, indicate the unparalleled power of Nowruz as an intercultural and convergent platform among these societies, whereby national or transnational media can consider Nowruz as an important cultural agenda in their diplomacy. The findings indicate that despite differences in geography, politics, and elites of the countries within the Nowruz civilization sphere, convergence is possible through the establishment of a Nowruz-based media union, the policy-making of dialogue-oriented macro and transnational media based on Nowruz dialogues, and the production of visual content, especially films and animations, regarding the historicity, culture, and discourse of Nowruz in the member countries of this sphere, which plays an undeniable and effective role